Human placental extract treatment for non‐alcoholic steatohepatitis non‐responsive to lifestyle intervention: A pilot study. Issue 9 (12th November 2014) - Shimokobe, Hideto; Sumida, Yoshio; Tanaka, Saiyu; Mori, Kojiro; Kitamura, Yoko; Fukumoto, Kohei; Kakutani, Akira; Ohno, Tomoyuki; Kanemasa, Kazuyuki; Imai, Shunsuke; Hibino, Sawako; Yoshikawa, Toshikazu
<x xml:space="preserve">Abstract</x> Aim No pharmacological therapies have been established for non‐alcoholic steatohepatitis (NASH), which can lead to liver‐related mortality. Human placental extract (HPE), which has anti‐inflammatory effects, has been expected to be a promising treatment for chronic liver disease. This pilot study was conducted to evaluate the efficacy of HPE for biopsy‐diagnosed NASH. Methods After a lifestyle intervention for 12 weeks, 10 subjects with abnormal alanine aminotransferase (≥30 IU/L) and biopsy‐proven NASH (Non‐Alcoholic Fatty Liver Disease Activity Score [NAS], ≥4) received i.m. injections of HPE (Laennec) at a dose of 4 mL/day twice per week for 24 weeks, and seven of them underwent a second liver biopsy after the treatment. Liver biopsies were scored for NAS and fibrosis. Histological response was defined as a decrease of 2 points or more in NAS and no increase in fibrosis. Results Serum transaminase activities were significantly lower at 8 weeks compared with pretreatment levels in nine patients who continued treatment for 24 weeks. One patient refused to continue the treatment soon after starting therapies. In seven patients undergoing post‐treatment biopsies, NAS (mean [standard deviation]) mildly decreased from 5.29 (0.95) to 4.00 (1.83) without reaching statistical significance (P = 0.078). Histological response was observed in all three obese patients and in only one of four non‐obese ones. No significant changes were observed in body mass index, lipid profiles and diabetic control/insulin resistance. Conclusion In NASH patients who received HPE treatment, significant reductions in serum liver enzymes were obtained after 8 weeks. Histological efficacy may be better in obese patients than in non‐obese ones.